Zaměření a vyhotovení účelové mapy v lokalitě přírodní památky Zlobice, Malhostovice - Petáková, Denisa (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Tato bakalářská práce se zabývá tvorbou účelové mapy v okolí přírodní památky Zlobice, Malhostovice. Práce obsahuje informace o lokalitě, přístrojích, hlavních použitých měřických metodách a následném zpracování. Výsledná účelová mapa je vyhotovena v měřítku 1:250 ve 3. třídě přesnosti dle ČSN 01 3410 v souřadnicovém systému S-JTSK a výškovém systému Bpv.

This bachelor thesis deals with the creation of a thematic map in the vicinity of the natural monument Zlobice, Malhostovice. The thesis contains information about the location, the measuring instruments, the main measurement methods and subsequent processing. The final thematic map is made in scale 1: 250 in the 3rd accuracy class according to ČSN 01 3410 in the coordinate system S-JTSK and the altitude system Bpv.
Survey and preparation of a large-scale map in the locality of the natural monument Zlobice, Malhostovice district
Keywords: účelová mapa; polygonový pořad; GNSS; totální stanice; Zlobice; Malhostovice; thematic map; polygon traverse; GNSS; total station; Zlobice; Malhostovice